2017
DOI: 10.1186/s40834-017-0042-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, acceptance and utilisation of the female condom among women of reproductive age in Ghana

Abstract: BackgroundThe female condom (FC) is the only safe and effective female-initiated method that provides simultaneous protection against unintended pregnancy as well as sexually transmitted infections (STIs), including HIV/AIDS. Knowledge of FC use among women and the perceptions and attitudes towards condom use can contribute to its uptake as an important public health strategy for HIV prevention in Ghana. However, there is a dearth of empirical evidence in this area of public health research to inform intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 24 publications
4
17
1
Order By: Relevance
“…Low awareness and perceptions of diseases among the population is known to negatively impact preventive measures (Ajayi et al, 2019;Ananga et al, 2017), which may influence early detection and acceptability to test for the SARS-CoV-2. Moreover, culture and religious beliefs of the people may also play a crucial role in accepting preventive measures taken to curb the spread of diseases (Spittel, Maier, and Kraus, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Low awareness and perceptions of diseases among the population is known to negatively impact preventive measures (Ajayi et al, 2019;Ananga et al, 2017), which may influence early detection and acceptability to test for the SARS-CoV-2. Moreover, culture and religious beliefs of the people may also play a crucial role in accepting preventive measures taken to curb the spread of diseases (Spittel, Maier, and Kraus, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Targeted FC promotion towards specific populations was perceived to facilitate increased uptake. Some argued that targeting young people (16)(17)(18)(19)(20)(21)(22)(23)(24)(25) would be best as they represent a group at risk of STIs. A couple of participants expressed the importance of familiarizing young people with the FC towards the beginning of their sexual history and believed that doing so would normalize FCs to young people: "…if they know that their friends are using it, …., then they would know "ah other people at my age are using it as well" (age 42, sexual health advisor).…”
Section: Education and Promotionmentioning
confidence: 99%
“…These include a lack of FC production and supply, higher cost compared to the MC, resistance from male partners, negative press, and minimal promotional efforts (11). A descriptive cross-sectional study (16) assessing Ghanaian women aged 15-49 years demonstrated low FC use, with only 48.4% of the 380 participants aware of FCs. This underutilisation may be explained by low FC accessibility and partner resistance, highlighting a gender power imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the FC has suffered from low demand, due to high cost, inadequate promotion and introduction by programs, and limited acceptability. This low acceptability of the FC includes pervasive male partner objection[3, 4]. However, studies suggest levels of protected sex increase when FCs are added to the available method mix[59].…”
Section: Introductionmentioning
confidence: 99%